Attention deficit hyperactivity disorder and drug addiction rehabilitation patients - Carlos Henrique Ferreira Camargo; Tarcísio Fanha Dornelles; Karin Barszcz; Eduardo Antunes Martins (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective Attention deficit hyperactivity disorder (ADHD) is characterized by a persistent pattern of inattention or hyperactivity. This study aimed to investigate the relationship between ADHD and drug dependence. Methods The presence and severity of ADHD and substance use were evaluated through questionnaires in 80 adult patients in therapeutic communities. Results No difference in drug use or dependence prevalence between ADHD and non-ADHD patients was found. However, ADHD patients had lower ages on admission (p = 0.004) and at first contact with cocaine (p = 0.033). In ADHD patients, there was a negative correlation between the age at first use of cannabis and the subsequent severity of cannabis use (p = 0.017) and cocaine use (p = 0.033). Conclusions Though there was no difference in prevalence of drug use among groups, results show that ADHD in patients in therapeutic communities may cause different addiction patterns, such as earlier use of cocaine and admission, and a more severe use of cocaine correlated to earlier contact with cannabis.